INFLUENCE OF COMPENSATION AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT PT VICTORY CHING LUH INDONESIA IN TANGERANG - Sigit Purnomo (Yayasan Education and Social Center, 2022)
This research aimed to determine the effect of compensation and work motivation on employee performance at PT Victory Ching Luh Indonesia Tangerang, either partially or simultaneously. Hypothesis testing and multiple regression are used in data analysis. The method used is the associative method. The sampling technique used is slovin sampling using a sample of 68 respondents. Other methods include validity and reliability tests and the classical assumption test. This study shows that compensation has a significant effect on employee performance with the regression equation Y = 5.099+0.928X1. The correlation coefficient value is 0.856, which means the two variables have a very strong relationship level with a coefficient of determination of 73.2%, and hypothesis testing is obtained t count > t table or (13,422>1,668). Work motivation significantly affects employee performance with the regression equation Y = 3.677+0.942X2. The correlation coefficient value is 0.942, meaning that both have a very strong relationship with a determination coefficient of 83.5%, and hypothesis testing is obtained t count > t table or (18.299>1.668). Compensation and work motivation simultaneously significantly affect employee performance with the regression equation Y = 3.409+0.072X1+0.879X2. The correlation coefficient values ​​obtained are 0.856 (X1) and 0.942 (X2), meaning that the compensation variable (X1) has a very strong relationship level and work motivation (X2) has a very strong relationship level to employee performance (Y) with a determination coefficient of 83,6%. In comparison, the remaining 16.4% is influenced by other factors. The calculated F value obtains hypothesis testing> F table or (65.663>2.750); thus, H0 is rejected, and H3 is accepted. This result means a significant simultaneous effect between compensation and work motivation on employee performance at PT Victory Ching Luh Indonesia Tangerang